a) Ta có:
4>3⇔√4>√3⇔2>√3⇔2.2>2.√3⇔4>2√34>3⇔4>3⇔2>3⇔2.2>2.3⇔4>23
Cách khác:
Ta có:
⎧⎨⎩42=16(2√3)2=22.(√3)2=4.3=12{42=16(23)2=22.(3)2=4.3=12
Vì 16>12⇔√16>√1216>12⇔16>12
Hay 4>2√34>23.
b) Vì 5>4⇔√5>√45>4⇔5>4
⇔√5>2⇔5>2
⇔−√5<−2⇔−5<−2 (Nhân cả hai vế bất phương trình trên với −1−1)
Vậy −√5<−2−5<−2.
a, Ta có : \(4=\sqrt{16}\); \(2\sqrt{3}=\sqrt{4.3}=\sqrt{12}\)
Do 12 < 16 hay \(2\sqrt{3}< 4\)
b, Ta có : \(-2=-\sqrt{4}\)
Do \(4< 5\Rightarrow\sqrt{4}< \sqrt{5}\Rightarrow-\sqrt{4}>-\sqrt{5}\)
Vậy \(-2>-\sqrt{5}\)
a) \(2\sqrt{3}=\sqrt{3\cdot2^2}=\sqrt{12}\); \(4=\sqrt{16}\)
Vì \(\sqrt{12}< \sqrt{16}\)=> \(4>2\sqrt{3}\)
b) \(-2=-\sqrt{4}\)
Vì \(\sqrt{4}< \sqrt{5}\)=> \(-\sqrt{4}>-\sqrt{5}\)hay \(-2>-\sqrt{5}\)
a)\(\sqrt{16}>2\sqrt{3}\)\(\leftrightarrow\)4>2\(\sqrt{3}\)
b)-\(-\sqrt{5}< \sqrt{4\Leftrightarrow}\) -\(\sqrt{5}\)<-2
a) Ta có:
nên
Vậy .
b) Ta có:
nên
Vậy .
a ) 4> 2 căn 3
b) - căn 5 < -2
a) Ta có:
Cách khác:
Ta có:
Vì
Hay .
b) Vì
(Nhân cả hai vế bất phương trình trên với )
Vậy
a) Ta có:
nên
Vậy .
b) Ta có:
nên
Vậy .
a) Ta có:
nên
Vậy .
b) Ta có:
nên
Vậy .
a) \(4=2.2=2.\sqrt{4}>2.\sqrt{3}\)
b)\(-\sqrt{5}< -\sqrt{4}=-2\)
a) 4 = \(\sqrt{16}\)
2\(\sqrt{3}\) = \(\sqrt{12}\)
Vì 16 > 12 ⇔ \(\sqrt{16}\) > \(\sqrt{12}\) ⇔ 4 > 2\(\sqrt{3}\)
b) Có 5 > 4 ⇔ \(\sqrt{5}\) > \(\sqrt{4}\) ⇔ -\(\sqrt{5}\) < -\(\sqrt{4}\) ⇔ \(-\sqrt{5}\) < \(-2\)
a) ta có :
\(2=\sqrt{4}>\sqrt{3}\) nên \(2.2>2\sqrt{3}\)
Vậy \(\sqrt{4}>2\sqrt{3}\)
b) Ta có:
\(\sqrt{5}>\sqrt{4}\) = 2 nên \(\sqrt{5}>2\Rightarrow-\sqrt{5}< -2\)
Vậy \(-\sqrt{5}< -2\)
\(\text{a) 4 và 2√3}\)
\(\text{Ta có: 2 = √4}\)
Vì \(4>3\Rightarrow\sqrt{4}>\sqrt{3}\Rightarrow2.\sqrt{4}>2\sqrt{3}\)
\(\Rightarrow4>2\sqrt{3}\)
Vậy \(4>2\sqrt{3}\)
b)\(-\sqrt{5}\) và \(-2\)
Ta có : \(2=\sqrt{4}\)
Vì \(5>4\Rightarrow\sqrt{5}>\sqrt{4}\Rightarrow-\sqrt{5}< -\sqrt{4}\)
\(\Rightarrow-\sqrt{5}< -2\)
Vậy \(-\sqrt{5}< -2\)
a) Ta có:
nên
Vậy .
b) Ta có:
nên
Vậy .
a) Ta có:
nên
Vậy .
b) Ta có:
nên
Vậy .
a) Ta có:
nên
Vậy .
b) Ta có:
nên
Vậy .
a) Ta có:
nên
Vậy .
b) Ta có:
nên
Vậy .